2018
DOI: 10.4314/ecajs.v22i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of paediatric burns patients at Maputo Central Hospital, Mozambique

Abstract: Background: The incidence of paediatric burn injuries is increasing in Africa. Paediatric burn injuries are among the leading causes of preventable morbidity and mortality in sub-Saharan Africa. Research on the morbidity and mortality in this setting is much needed. Methods: We conducted a prospective questionnaire-based analysis of paediatric burn patients presenting to the Maputo Central Hospital during a five-month period. Interviews were conducted with the children's caretakers by 2 paediatric surgery resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In this study, other Gram-negative rods such as E. coli , Proteus mirabilis , and Enterobacter spp. were also observed in very low frequencies, similar to reports from other studies [ 8 , 10 ]. The differences in the causative bacteria of BWI could be explained by the difference in geographic environment and infection control measures [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, other Gram-negative rods such as E. coli , Proteus mirabilis , and Enterobacter spp. were also observed in very low frequencies, similar to reports from other studies [ 8 , 10 ]. The differences in the causative bacteria of BWI could be explained by the difference in geographic environment and infection control measures [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…The deaths were attributed to inappropriate antibiotic use due to delays in laboratory testing including wound swab and blood culture that might have resulted in septicemia and eventually death [ 6 ]. In studies involving pediatric patients, sepsis was found to be the leading cause of death in Mozambique (100%) and the second cause of death in Cameroon (24%) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%